2006
DOI: 10.1002/chem.200600007
|View full text |Cite
|
Sign up to set email alerts
|

Activating an Enzyme by an Engineered Coiled Coil Switch

Abstract: We designed a de novo protein based on a circular permutant of RNaseT1, in which the enzymatic activity can be manipulated by engineered peptide binding. The circular permutant of RNaseT1 was obtained by tethering the original C- and N-termini with a GPAG linker and cleaving the molecule between Glu82 and Asn83. This mutant lacked enzymatic activity, due to the destabilization of entire protein structure. We previously reported the construction of ABC-type heterotrimeric coiled coil peptides, in which the A- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Coiled-coils have seen a diverse array of applications in biomaterials, affinity purification, assembly of bispecific or high avidity antibodies, and reconstitution of various split proteins or dimerizationdependent protein complexes 29,30 . Conditionally dimeric coiled-coil fusions have previously been used to reconstitute and control a split mutant of RNAse T1 31 and to conditionally enact DNA binding by a bZIP domain upon photostimulation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Coiled-coils have seen a diverse array of applications in biomaterials, affinity purification, assembly of bispecific or high avidity antibodies, and reconstitution of various split proteins or dimerizationdependent protein complexes 29,30 . Conditionally dimeric coiled-coil fusions have previously been used to reconstitute and control a split mutant of RNAse T1 31 and to conditionally enact DNA binding by a bZIP domain upon photostimulation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka and colleagues inserted two out of three helices from a hetero-specific coiled-coil trimer into a circularly permuted version of RNaseT1. They showed that adding the missing helix could constitute the trimer, and with it the enzyme [30]. Reversible photo-activation of coiled-coil transcription factor binding to DNA has also been demonstrated [31].…”
Section: Novel Structures Switches and Functionsmentioning
confidence: 99%
“…1517 Specific examples of Ar-containing de novo and engineered CCs include: engineered pentameric barrels containing buried Trp or Phe residues (Figure 1C), 20,21 and heterotrimeric CCs with a buried Trp. 2224 More recent examples include various parallel and antiparallel helical bundles with consolidated cores that feature Phe residues, 2527 and homomeric and heteromeric helix-loop-helix motifs with isolated Tyr, His and Trp residues that contribute to buried hydrogen-bond networks (Figure 1D & E). 14…”
Section: Figurementioning
confidence: 99%